The dimensions of national competitiveness: The empirical analysis based on The World Economic Forum’s data - Adamkiewicz, Hanna G. (Economics and Business Review, 2019)
The aim of this research is to determine the minimum number of uncorrelateddimensions which can describe national competitiveness (NC). NC is thoughtof as the ability of a nation to provide a conducive environment for its firms to prosper.It is shown that the environment affects national productivity catalytically throughthe interactions with the production factors while itself remaining unchanged. SelectedWorld Economic Forum’s indicators are used for determining the components of theenvironment. The Principal Component Analysis has revealed three orthogonal dimensionsof NC. Countries are represented by the points in the three-dimensionalspace. The weighted Euclidean distance from the origin to the ith point is proposed asa novel measure of the ith country’s level of NC.